Strategic Implementation of Cloud Technology in the Financial Sector - Gruner, Toni Jonas; Taušer, Josef; de Batz de Trenquelléon, Laure Sabine Marie; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This dissertation examines the strategic implications of adopting cloud computing in the financial industry, with a specific focus on its impact on organizational performance and market competitiveness. Adopting an integrative research approach comprising literature synthesis, expert interviews, and a theoretical case study, this research outlines both the benefits and challenges of cloud integration. Through the application of the Resource-Based View (RBV) and Dynamic Capabilities theories, the study assesses cloud technology as a strategic resource and an enabler of innovation, flexibility, and operational efficiency. Key findings reveal that the adoption of cloud solutions reduces IT costs, enhances service delivery, and enables real-time data analysis, consequently enriching customer experiences and enabling financial institutions to respond promptly to market dynamics. However, the migration to cloud computing presents several complexities, such as the necessity of data security, compliance with regulatory requirements, and compatibility with installed legacy systems. The dissertation concludes by giving practical guidance to organizations seeking to adopt cloud technologies strategically, in addition to calling for further research on the long-term implications and regional regulatory aspects.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses